1999
DOI: 10.1677/joe.0.1620237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic bromocriptine (CB-154) treatment on the plasma glucose and insulin secretion response to neurocytoglucopenia in rats

Abstract: Neurocytoglucopenia has been reported to increase both parasympathetic and sympathetic tone with a predominant effect on the latter, which accounts for the major effect of plasma hyperglycemia and the inhibition of insulin secretion. The aim of this study was to determine the effects of chronic treatment with bromocriptine (0·4 mg/100 g body wt per day), a potent sympatholytic D 2 -dopaminergic agonist, on hyperglycemia and insulin secretion in response to neurocytoglucopenia induced by 2-deoxy--glucose (2DG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…34 Similar data have been described with chronic bromocriptine treatment increasing parasympathetic response to neuroglucopenic stress. 8 In the present study, it has also been observed that plasma triglyceride neuroglucopenic stress response was significantly modified by the chronic enalapril treatment. In enalapril-treated rats, an increase in triglyceride levels was observed after 2DG infusion while the controls showed no alteration of plasma triglyceride levels.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…34 Similar data have been described with chronic bromocriptine treatment increasing parasympathetic response to neuroglucopenic stress. 8 In the present study, it has also been observed that plasma triglyceride neuroglucopenic stress response was significantly modified by the chronic enalapril treatment. In enalapril-treated rats, an increase in triglyceride levels was observed after 2DG infusion while the controls showed no alteration of plasma triglyceride levels.…”
Section: Discussionsupporting
confidence: 73%
“…Neuroglucopenic stress was induced by infusion of 50 mg/100 g of 2-deoxy-D-glucose 10% solution. 8 The animals were divided into three experimental groups: control rats submitted to neuroglucopenic stress (VD), enalapriltreated rats subjected to neuroglucopenic stress (ED), and enalapril-treated rats receiving NaCl 0.9% infusion instead of 2DG solution (ES).…”
Section: Experimental Designmentioning
confidence: 99%
“…p.o. [8]. Group 4 (Sub therapeutic): treated with the sub therapeutic doses of both test (bromocriptine in a dose of 2 mg/kg body wt) and standard (glipizide in a dose of 1.25mg/kg body wt) drugs p.o.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 The D 2 receptors have been involved in adrenal regulation and response to stressful stimuli, in addition to their classical role in prolactin-secreting adenomas. [8][9][10][11][12][13][14][15] Indeed, the dopaminergic agents have been the mainstay in the treatment of prolactinomas, through an action on the D 2 receptors. 16 Furthermore, somatotroph pituitary tumors occasionally show dramatic anti-secretory and anti-proliferative responses to dopaminergic agents.…”
Section: Commentarymentioning
confidence: 99%